2020
DOI: 10.1021/acs.jafc.0c02245
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly Water-Based λ-Cyhalothrin Polydopamine Microcapsule Suspension with High Adhesion on Leaf for Reducing Pesticides Loss

Abstract: Recently, innovations of nano/microcarrier formulations have been focused on improving application efficiencies and retention time. In this study, a water-based 2.5% λ-cyhalothrin (LC) microcapsule suspension (CS) was developed by orthogonal test with biodegradable and adhesive polydopamine (PDA) microcapsules (MCs) as carriers. The obtained LC-PDA CS had good suspension properties, flow behavior, storage stability, and rheological properties. LC-PDA CS had higher retention, wettability, and decreased rainwate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…31 The 96 h LC 50 of the same LC/PDA-MS with respect to Danio rerio was reported as 7.5 × 10 −3 mg/L. 22 In this study, we found that microcapsule LC/PDA-MS is weakly toxic to E. sinensis, with a mean 96 h LC 50 of 6.4 mg/L (with a corresponding 96 h LC 50 value of 161 μg/L with respect to LC in unencapsulated form). Such a high tolerance of crabs to this pesticide can be attributed to the environmentally friendly PDA microcapsule delivery, which lowers the toxicity of LC.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…31 The 96 h LC 50 of the same LC/PDA-MS with respect to Danio rerio was reported as 7.5 × 10 −3 mg/L. 22 In this study, we found that microcapsule LC/PDA-MS is weakly toxic to E. sinensis, with a mean 96 h LC 50 of 6.4 mg/L (with a corresponding 96 h LC 50 value of 161 μg/L with respect to LC in unencapsulated form). Such a high tolerance of crabs to this pesticide can be attributed to the environmentally friendly PDA microcapsule delivery, which lowers the toxicity of LC.…”
Section: Discussionsupporting
confidence: 88%
“…Then, a 2.5% LC/PDA-MS suspension was prepared by mixing the dispersant and xanthan gum with antifoam in an aqueous solution. 22 2.3. Acute Toxicity Test.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations